2020
DOI: 10.1021/acs.inorgchem.0c01124
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphous Indium Metal–Organic Frameworks Based on a Ferrocene Linker: Redox Activity, Porosity, and Structural Diversity

Abstract: The metallocene-based linker molecule 1,1′-ferrocenedicarboxylic acid (H2FcDC) was used to synthesize four different polymorphs of composition [In­(OH)­(FeC12H8O4)]. Using conventional solvent-based synthesis methods and varying the synthetic parameters such as metal source, reaction temperature, and solvent, two different MOFs and one 1D-coordination polymer denoted as CAU-43 (1), In-MIL-53-FcDC_a (2), and In-FcDC (3) were obtained. Furthermore, thermal treatment of CAU-43 (1) at 190 °C under vacuum yielded a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 54 publications
1
28
2
Order By: Relevance
“…The structural flexibility of MlL‐53 frameworks with different types of linker molecules is well known. In the case of FcDC 2− based MOFs, different aluminum and indium based compounds were reported which did not show any kind of breathing behavior or structural flexibility depending on external stimuli such as temperature or guest molecules so far [31,32] . In comparison to these isostructural compounds, Ga‐MIL‐53‐FcDC shows structural flexibility depending on which guest molecule is located in the channels of the framework.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The structural flexibility of MlL‐53 frameworks with different types of linker molecules is well known. In the case of FcDC 2− based MOFs, different aluminum and indium based compounds were reported which did not show any kind of breathing behavior or structural flexibility depending on external stimuli such as temperature or guest molecules so far [31,32] . In comparison to these isostructural compounds, Ga‐MIL‐53‐FcDC shows structural flexibility depending on which guest molecule is located in the channels of the framework.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of FcDC 2À based MOFs, different aluminum and indium based compounds were reported which did not show any kind of breathing behavior or structural flexibility depending on external stimuli such as temperature or guest molecules so far. [31,32] In comparison to these isostructural compounds, Ga-MIL-53-FcDC shows structural flexibility depending on which guest molecule is located in the channels of the framework. During the solvent exchange procedure for activation, obvious changes in the peak intensity and positions can be observed, indicating structural flexibility of the MOF (Figure 6).…”
Section: Structural Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The metallocene family is composed of central transition metal atoms and organic cyclopentadienyl groups (Goodwin et al, 2021). Among of them, ferrocene, which is aromatic and contains easily replaced sites, shows a high redox activity in the field of electrochemistry (Benecke et al, 2020). Using this advantage, Mi et al proposed to covalently anchor ferrocene on the graphene oxide, as shown in Figure 2A (Mi et al, 2016).…”
Section: Metal-organic Hybrid Electrocatalystsmentioning
confidence: 99%
“…The synthesis and the design of coordination polymers (CPs) have attracted extensive interest with their wonderful performances and architectures from a variety of molecular building blocks linked via supramolecular contacts and coordination bonds, owing to their latently extensive applications in the functional materials [4][5][6][7]. Many remarkable spectacular coordination polymers have been recorded, for instance, 1D ladders and chains, two-dimensional grids, as well as 3D helical staircase networks, interpenetrated modes, and the microporous networks [8][9][10][11]. Among the above MOFs, recently, special attention has been paid to systems with single motifs entanglements.…”
Section: Introductionmentioning
confidence: 99%